Freedom and Equality Problems in Indonesia’s Democracy - Harahap, Husnul Isa; Ekayanta, Fredick Broven (Jurnal Politik, 2023)
What part of democracy is the most frequently an issue in a democratic country? It is freedom and equality. This book contains a collection of articles that repeat more or less the same questions. Likewise, the answer is still around the problems of freedom (speech, politics, opinion, competition, power, press, expression.) and equality (law, social rights, and other aspects.). The difference is in its perspectives and cases, as it differs in place, condition, and time.